1995
DOI: 10.1111/j.1432-1033.1995.tb20411.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Rat m3 Muscarinic Acetylcholine Receptor Produced in Insect Cells Infected with Recombinant Baculovirus

Abstract: ThLe m3 muscarinic acetylcholine receptor from rat heterologously produced in insect cells after infection with a recombinant baculovirus has an apparent molecular mass of approximately 75 kDa. Polyclonal antibodies raised against a carboxy-terminal nonapeptide that is unique to the m3 subtype can detect the receptors produced in the insect cells by Western blot and can also immunoprecipitate solubilized receptor. Immunofluorescence microscopy as well as electron microscopy revealed that the receptor was locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 41 publications
4
16
0
Order By: Relevance
“…Previous reports suggested that a portion of recombinant membrane proteins, including G-coupled receptors, produced in Sf9 cells does not reach the cell surface but remains in the endoplasmic reticulum and Golgi compartments because of possible saturation of the translocation machinery of the insect cell (22)(23)(24)(25). This hypothesis is also supported by our immunofluorescence experiments on permeabilized Sf9 cells expressing hMOR-his in which antibody labeling was detected not only at the cell surface but also inside the cell.…”
Section: Effect Of the Amino-terminal Histidine Tag On Receptor Expresupporting
confidence: 87%
“…Previous reports suggested that a portion of recombinant membrane proteins, including G-coupled receptors, produced in Sf9 cells does not reach the cell surface but remains in the endoplasmic reticulum and Golgi compartments because of possible saturation of the translocation machinery of the insect cell (22)(23)(24)(25). This hypothesis is also supported by our immunofluorescence experiments on permeabilized Sf9 cells expressing hMOR-his in which antibody labeling was detected not only at the cell surface but also inside the cell.…”
Section: Effect Of the Amino-terminal Histidine Tag On Receptor Expresupporting
confidence: 87%
“…The hydrophilic antagonist N-methylscopolamine afforded little or no protection when added at the time of infection. It therefore appears that the functional oligomers obtained upon treatment with quinuclidinylbenzilate derived largely from intracellular compartments, in accord with the observation that the localization of muscarinic receptors in Sf9 cells is largely intracellular (Vasudevan et al 1995).…”
Section: Discussionsupporting
confidence: 53%
“…These include the V2 vasopressin receptor (this study, Fig. 3), platelet-activating factor receptor (46), metabotropic glutamate receptor (47), substance P receptor (48), neurokinin-2 receptor (49), the C5a anaphylaxotoxin receptor (50), glucagon receptor (14), the dopamine D1 receptor (43), D2 receptor (44), the 5HT 1B receptor (45), the M2 muscarinic receptor (12), and the M3 muscarinic receptor (52). Therefore, it is clear that receptor-specific determinants for dimerization must exist.…”
mentioning
confidence: 96%